2011
DOI: 10.1128/aac.01219-10
|View full text |Cite
|
Sign up to set email alerts
|

T-705 (Favipiravir) Inhibition of Arenavirus Replication in Cell Culture

Abstract: A number of New World arenaviruses (Junín [JUNV], Machupo [MACV], and Guanarito [GTOV] viruses)can cause human disease ranging from mild febrile illness to a severe and often fatal hemorrhagic fever syndrome. These highly pathogenic viruses and the Old World Lassa fever virus pose a significant threat to public health and national security. The only licensed antiviral agent with activity against these viruses, ribavirin, has had mixed success in treating severe arenaviral disease and is associated with signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
74
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(86 citation statements)
references
References 27 publications
(33 reference statements)
10
74
0
2
Order By: Relevance
“…This is in line with the activity against the influenza virus RNA-dependent RNA polymerase reported by Kiso et al (50) and with data reported for the chikungunya virus, in which a single mutation in the polymerase protein was sufficient to make the virus resistant to treatment (47). Although it is possible that T-705 interferes with viral morphogenesis at a late stage of the infectious cycle, T-705 is a nucleotide analog, and its mechanism of action is thought to be related to the selective inhibition of viral RNA-dependent RNA polymerases of influenza virus and many other RNA viruses (21,23 (32,51). However, the exact mechanism of action against paramyxoviruses still remains to be elucidated.…”
Section: Discussionmentioning
confidence: 80%
“…This is in line with the activity against the influenza virus RNA-dependent RNA polymerase reported by Kiso et al (50) and with data reported for the chikungunya virus, in which a single mutation in the polymerase protein was sufficient to make the virus resistant to treatment (47). Although it is possible that T-705 interferes with viral morphogenesis at a late stage of the infectious cycle, T-705 is a nucleotide analog, and its mechanism of action is thought to be related to the selective inhibition of viral RNA-dependent RNA polymerases of influenza virus and many other RNA viruses (21,23 (32,51). However, the exact mechanism of action against paramyxoviruses still remains to be elucidated.…”
Section: Discussionmentioning
confidence: 80%
“…T-705 was shown to have different characteristics from amantadine and neuraminidase inhibitors. T-705 strongly inhibits the replication of influenza virus types A, B, and C and has broad-spectrum activities against various RNA viruses, such as arenaviridae, bunyaviridae, flaviviridae, picornaviridae, and paramyxoviridae (4,(7)(8)(9)(10)(11). T-705 is currently undergoing phase II clinical trials for the treatment of influenza virus infections in the United States.…”
mentioning
confidence: 99%
“…T-705, an RNA-dependent RNA polymerase inhibitor, was also reported to have antiviral activity against a variety of RNA viruses. It is under development as a therapeutic candidate; however, its potency (50% inhibitory concentration [IC 50 ]) falls in the few hundred micromolar range for most viruses, with the exception of influenza viruses (7).…”
mentioning
confidence: 99%